2021
DOI: 10.3390/children8100882
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Room Care for Premature Infants Born after Less than 25 Weeks’ Gestation—A Narrative Review

Abstract: Premature infants born after less than 25 weeks’ gestation are particularly vulnerable at birth and stabilization in the delivery room (DR) is challenging. After birth, infants born after <25 weeks’ gestation develop respiratory and hemodynamic instability due to their immature physiology and anatomy. Successful stabilization at birth has the potential to reduce morbidities and mortalities, while suboptimal DR care could increase long-term sequelae. This article reviews current neonatal resuscitation guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
(168 reference statements)
0
4
0
Order By: Relevance
“…Infants born at 22-24 weeks of GA benefit from a standardized approach to initial stabilization after birth to reduce unwarranted variability in care [6]. [[,21] Basic neonatal resuscitation guidelines should apply for all gestational ages with the main priority to establish a normal gas exchange by recruiting optimal functional residual capacity immediately after birth [22,23].…”
Section: Delivery Room Managementmentioning
confidence: 99%
“…Infants born at 22-24 weeks of GA benefit from a standardized approach to initial stabilization after birth to reduce unwarranted variability in care [6]. [[,21] Basic neonatal resuscitation guidelines should apply for all gestational ages with the main priority to establish a normal gas exchange by recruiting optimal functional residual capacity immediately after birth [22,23].…”
Section: Delivery Room Managementmentioning
confidence: 99%
“…Over the last decade, new efforts have been done to explore optimal approaches in the management of the extreme preterm infant in the delivery setting. Schwaberger et al [ 2 ] explore current guidelines and explore challenges currently existing while Law et al [ 3 ] present a pilot feasibility trial which forms the basis of an upcoming large international clinical trial set to start recruitment in 2022.…”
mentioning
confidence: 99%
“…Last year, several articles on different aspects related to neonatal resuscitation were published in the journal Children. The topics covered included staff training [ 1 , 2 ], technological aspects [ 3 , 4 , 5 , 6 ], and the investigation of “new” clinical interventions [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
mentioning
confidence: 99%
“…The aspects related to the outcome of peri-viable infants born at 22–25 weeks’ gestational age was reported in a well-written review [ 9 ] and an observational single center cohort study from Taiwan [ 10 ]. The authors of the latter study reported a significant increase in the survival of peri-viable extremely low-gestational age infants after the implementation of the 2015 American Academy of Pediatrics Neonatal Resuscitation Program, which advocated a change in the threshold of viability from 23 weeks’ to 22 weeks’ gestation.…”
mentioning
confidence: 99%